Literatura de cordel: letra, imagem e corpo em diálogo - Dizioli, Irene Gloe (2009)
The cordel literature, meaningful expression of the Northeast s popular culture, has engendered an increasing interest in the academic literature after a period of forgetfulness. This paper attempts to appraise this plural artistic expression. Starting from a historical comprehension through questions related to its original poetry position, with its formal models, focusing in the orality and in the performance, and finishing with its participation also as an art of the memory. This work is organized in four chapters. All of them, especially the first one, were based on the Paul Zumthor s theoretical assumptions and in his inquiring and innovative thoughts about memory, orality and performance. The first chapter is the core of the reflections presented in this paper. The second chapter presents a historical path, while the third chapter focuses in the critics. Through an analysis and review of the classical paper Viagem ao país de São Saruê , de Manoel Camilo dos Santos, chapter four presents an example of a cordel text model. It is also considered useful a modernization of the media structure used by the new cordel poets